The level of Emotional intelligence of educational Advisors in Karak governorate(field study) - Al-Mayttah, Mutasim (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The study aimed to identify the level of emotional intelligence of educational supervisors in Karak governorate, and whether there are differences in emotional intelligence due to gender and years of service. In order to achieve the objectives of the study, (Abdo and Othman) emotional intelligence measurements were used. The study population consisted from (162) educational supervisors in Karak governorate. The survey sample excluded (20) mentors and (8) questionnaires were excluded due to their lack of validity for analysis. The study applied on (134) advisers. The sample was selected in the comprehensive inventory, and was based on the descriptive method. The study reached a number of results such as: The level of emotional intelligence among the educational supervisors in Karak governorate is high. The field of emotion regulation ranked came first, secondly came the field of empathy, thirdly came the social communication, fourthly came emotion management, and finally came emotional knowledge at a high level. The study also found that there were no statistically significant differences at the level of (α0.05) in the level of emotional intelligence of educational supervisors due to gender. The results also indicated that there were statistically significant differences at the level of (α0.05) in the level of emotional intelligence of the educational supervisors due to years of experiences. The differences were in favor of those who served for 15 years or more at the expense of those whose service was less than 5 years or Less than 10 years.